IMPAIRED ANKLE BRACHIAL INDEX AND UNFAVORABLE AMBULATORY BLOOD PRESSURE PROFILE IN PATIENTS WITH HOSPITALIZED FOR MYOCARDIAL INFARCTION. (June 2018) - Konstantinou, K.; Tsioufis, K.; Mantzouranis, M.; Koumelli, A.; Fragoulis, C.; Vogiatzakis, N.; Dimitriadis, K.; Kasiakogias, A.; Tousoulis, D.
Abstract : Objective: The aim of the present study was to assess the vascular status as assessed by ankle brachial index (ABI) and ambulatory blood pressure (BP) profile in patients hospitalized for myocardial infarction. Design and method: We studied 75 patients (76% males, age 65 ± 13 years) who were hospitalized because of ST-elevation myocardial infarction (STEMI) and Non ST–elevation myocardial infarction (NSTEMI). All patients underwent baseline estimation of clinical and laboratory parameters during their hospitalization. Moreover, ABI was measured according to established methodology and patients underwent 24-hour ambulatory BP monitoring during the third day of hospital stay. Results: From the total population, 20% had family history of cardiovascular events, 72% were hypertensives, 32% had diabetes, 51% were smokers and 32% had previous history of coronary artery disease. Regarding the type of myocardial infarction, 37% were admitted for STEMI and 55% had coronary revascularization. Focusing on the ABI the levels in the entire population was 1.04 ± 0.25, while 36% of patients had impaired ABI < 0.9. Mean 24-h BP was 1156/69 mmHg, while 59 patients (78%) presented a non-dipping profile. Conclusions: Patients admitted for STEMI and NSTEMI are characterized by impaired ABI and high prevalence of non-dipping of BP during nighttime. These findings may explain the unfavorable overall cardiovascular prognosis of these patients.